Phosphoproteomics Reveals Key Regulatory Kinases and Modulated Pathways Associated with Ovarian Cancer Tumors - Hu Y (OncoTargets and Therapy, 2020)
Yingchao Hu,1 Lejia Sun,2 Yinglan Zhang,3 Jinghe Lang,1 Jun Rao4 1Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100730, People’s Republic of China; 2Department of Liver Surgery, Peking Union Medical College (PUMC) Hospital, PUMC & Chinese Academy of Medical Sciences, Beijing 100730, People’s Republic of China; 3Department of Obstetrics and Gynecology, Affiliated Beijing Chaoyang Hospital of Capital Medical University, Beijing 100020, People’s Republic of China; 4Jiangxi Provincial Key Laboratory of Translational Medicine and Oncology, Jiangxi Cancer Hospital, Jiangxi Cancer Center, Nanchang 330029, People’s Republic of ChinaCorrespondence: Jinghe Lang; Jun Rao Email langjh2019@126.com; 312438124@qq.comBackground: Ovarian cancer (OC) is the seventh most common cancer worldwide for women. However, there are no sufficient diagnostic methods and few treatment options available due to poor understanding of its pathogenic mechanisms.Methods: To comprehensively analyze the phosphoproteomic characterization for OC, we took advantage of a quantitative global phosphoproteomics method, titanium(IV) immobilized metal affinity chromatography (Ti4+-IMAC) coupled to nanoscale liquid chromatography and quadrupole time-of-flight tandem mass spectrometry (nanoLC/Q-TOF-MS/MS) on ovarian tissue samples obtained from five OC patients and five matched controls.Results: A total of 722 phosphorylated sites corresponding to 534 proteins were significantly different (fold change ≥ 2, p < 0.01) between OC patients and the controls. Among them, 83 transcription factors mainly consisted of transcription cofactors, zf-C2H2, and chromatin remodeling factors and 29 kinases were included. Further functional analysis suggested significantly biological processes were highly enriched and involved in the pathogenesis of OC, especially fructose and mannose metabolism. Moreover, the regulatory roles of modulated pathways, including MAPK, ErbB, and GnRH signaling pathways were also identified as critical processes involved in OC. The results here highlighted key phosphorylated proteins, particularly kinases, and the corresponding cancer-related metabolic and signal pathways that played important roles in the development of OC. Additionally, the expression levels of two kinases, phosphorylated CDK (T14) and phosphorylated PRKCQ (S695), were validated by Western blot analysis in the other group of ovarian tissue samples.Conclusion: Altogether, our data not only provided novel insights into the potential biomarkers and therapy options for OC but also extended our knowledge on its pathophysiological mechanism.Keywords: ovarian cancer, phosphoproteomics, Ti4+-IMAC, kinases, biomarker